2021
DOI: 10.30684/etj.v39i1a.1704
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Investigations of Double Pass Solar Air Heater with Two Types of Porous Media of Different Thermal Conductivity

Abstract: This study describes an experimental investigation of the thermal efficiency of stainless steel mesh and steel wool as a porous medium in the lower channel of a double pass solar air heater. An experimental setup was planned and developed. Various types of porous media with high thermal conductivity and with different porosities have been tested. The effects of the porosity of wire mesh, the thermal conductivity of porous media, mass flow rate, and the intensity of radiation have been studied. Experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…From Figure 8b, it can be concluded that decreasing the porosity can improve the efficiency; this is because the reduction in porosity can increase the heat transfer area per unit volume. This finding is in agreement from those in [11,50,51]. In addition, decreasing the porosity produces a larger surface area for heat transfer, and the higher volumetric heat-transfer coefficient greatly improved due to flowing air turbulence.…”
Section: Determination Of the Optimum Porositysupporting
confidence: 90%
“…From Figure 8b, it can be concluded that decreasing the porosity can improve the efficiency; this is because the reduction in porosity can increase the heat transfer area per unit volume. This finding is in agreement from those in [11,50,51]. In addition, decreasing the porosity produces a larger surface area for heat transfer, and the higher volumetric heat-transfer coefficient greatly improved due to flowing air turbulence.…”
Section: Determination Of the Optimum Porositysupporting
confidence: 90%
“…The maximum temperature difference when using steel wire mesh reaches 34 o C at porosity 99.995%, meanwhile, the maximum temperature difference when using Aluminum reach 41 o C at porosity 99.997% as shown in Figures (11) (12). The maximum efficiency when using steel wire mesh reaches 67.4% at porosity 99.995%, meanwhile the maximum efficiency when using Aluminum reaches 79.4% at porosity 99.997% as shown in Figures (13)…”
Section: Resultsmentioning
confidence: 90%
“…For flow rates less than 0.2 L/s, Nano fluid usage at low concentrations might improve thermo-hydraulic performance. Jalal M. Jalil et al [13] investigated the effect of porous medium in the lower channel of double pass air heater solar collector, used stainless steel wire mesh and steel wool as porous medium, founded enhancement in thermal efficiency.the thermal performance of the double passage water in the evacuated tube in the parabolic trough collector is being studied by a variety of porous media, porosity, mass flow rates and solar radiation. The main objective is to increase parabolic trough collector thermal performance that may be utilized to heat water.…”
Section: Introductionmentioning
confidence: 99%
“…Single-pass SAHs produced a better rise in temperature at the outlet by inserting a partially filled wire mesh in a number of studies: Abed et el. [24] utilised a 'U'-type arrangement of aluminium wire mesh and compared it with 'V'-type soft steel wire mesh as a corrugated absorber; Devecioglu et al [25] utilised a copper wire mesh at four equal distances in the vertical direction, i.e., keeping perpendicular to the absorber plate; Ghritlahre et al [26] and Rajarajeswari et al [27] utilised a mesh in the diagonal direction lower side at the inlet and upper side at the outlet of an SAH; Sozen et al [28] utilised an iron wire mesh, keeping at 100 mm equal intervals of distance perpendicular to the absorber plate; and Jalil and Ali [29] utilised steel wool and six layers at equal distances of stainless steel wire mesh, which improved the thermal performance of a single-pass SAH.…”
Section: Introductionmentioning
confidence: 99%